An Analysis of students’ anxiety factors of EFL students’ Speech Production - zahratul fikni (Jurnal Langua, 2022)
English Foreign Learners (EFL) students are considered to master English when the students can speak in English fluently which can be seen from their speech production. Nevertheless, becoming fluently competent is particularly difficult for foreign language learners as it is influenced by a number of factors. Among the several factors which affect foreign language learning especially speaking, anxiety emerges to be the crucial one that has a debilitating effect on the oral performances of students. This study was purposed to analyse speaking anxiety level and factors of English Foreign Language student’s anxiety in speech production. The data were gathered from qualitative research with random sampling conducted on the second semester consist of 30 students taking Speaking for Academic Communication class at Hamzanwadi University. A closed-ended questionnaire of Foreign Language Classroom Anxiety Scale and semi-structured interviews was administered to the participants to explore the anxiety level and the factors of their anxiety in speech production. The results show severe anxiety level which indicated that students are highly anxious when speaking English. Furthermore, the findings revealed that the factors contributed to the students’ speaking anxiety were shyness with audience, fear of not being able to convey the message well, lack of preparation, low self-confidence and low-proficiency. Keywords: foreign language anxiety, speaking anxiety, speech production, anxiety factors